2006
DOI: 10.1016/j.ygeno.2005.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Capucin: A novel striatal marker down-regulated in rodent models of Huntington disease

Abstract: In an initial study, we compared quantitative transcriptome data across mouse brain territories using the serial analysis of gene expression method. Among the novel regional markers that we discovered, we focused on a striatum-enriched transcript with no available experimental cDNA sequence. Here, we report its cloning, gene structure, and detailed distribution in mouse brain. Quantitative RT-PCR and in situ hybridization demonstrated predominant expression in dorsolateral striatum. We therefore named it capuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…Sequence similarity to SynDIG1 was observed for three genes in the mouse genome with the highest degree of identity within the second half of the protein, including the two hydrophobic segments (Figure S1). The only related protein in mouse that has been characterized is referred to as “capucin” to reflect its predominant expression in caudate and putamen of the dorsolateral striatum (de Chaldee et al, 2006). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sequence similarity to SynDIG1 was observed for three genes in the mouse genome with the highest degree of identity within the second half of the protein, including the two hydrophobic segments (Figure S1). The only related protein in mouse that has been characterized is referred to as “capucin” to reflect its predominant expression in caudate and putamen of the dorsolateral striatum (de Chaldee et al, 2006). …”
Section: Resultsmentioning
confidence: 99%
“…Capucin localizes to the Golgi compartment in heterologous cells (de Chaldee et al, 2006). To determine if SynDIG1 also localizes to Golgi structures, the distribution of HA-SynDIG1 was analyzed in COS cells with immunocytochemistry.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…de Chaldee et al used Serial Analysis of Gene Expression (SAGE) to identify capucin (caudate-and putamen-enriched sequence) (de Chaldee et al, 2006). Capucin mRNA distribution exhibits a strikingly restricted pattern, detectable only in brain and, to a lesser extent, in testis, and essentially confined to the striatum.…”
Section: Other Moleculesmentioning
confidence: 99%
“…Notably, lower capucin mRNA levels have been detected in the R6/1 transgenic mouse model of HD (Desplats et al, 2006), R6/2 and in primary cultures of rat striatal neurons expressing a mutant fragment of human Htt than in the corresponding controls (de Chaldee et al, 2006). However, in vivo experiments showed that capucin overexpression is not able to counterbalance mHtt-induced toxicity in the striatum in a lentiviral mouse model of HD (Galvan et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%